Management of Bos Funds to Improve Quality Learning in Elementary Schools - Mismariat Mismariat; Bahrun Bahrun; Nasir Usman; Dedi Sartana (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Research on the management of School Operational Assistance (BOS) funds is very important because it plays a strategic role in ensuring the effective use of the education budget to improve the quality of learning in elementary schools. This study aims to determine how School Operational Assistance (BOS) management improves the quality of the learning process in elementary schools. A qualitative approach was used, with data collection techniques including observation, interviews, and documentation. Data sources were determined using purposive sampling, with participants consisting of school supervisors, principals, vice principals, school treasurers, and teachers. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing or verification. The results of the study indicate that the management of BOS funds in elementary schools is carried out effectively, accountably, and in accordance with regulations. The planning process was carried out participatively through a needs analysis outlined in the RKAS (School Activity and Budget Plan), organization was carried out with a clear division of tasks, and implementation followed technical guidelines with the main allocation going to the development of infrastructure and extracurricular activities. Supervision was carried out internally and externally to ensure transparency and accountability. Overall, the management of BOS funds has a positive impact on the quality of learning and student development, including in strengthening Islamic educational values such as honesty, trustworthiness, responsibility, and cooperation in school financial management. Thus, the successful management of BOS funds not only reflects administrative effectiveness but also embodies the implementation of Islamic values in creating an education management system that is both ethical and fair.